El giro etnográfico. Apuntes sobre una categoría emergente en la literatura argentina contemporánea (El Hilo de la Fabula, 2021)
This article develops a critical analysis of the implementation of the narrative category of ethnofiction by the cultural anthropologist Marc Augé in confrontation with the ethnographic turn identified by Beatriz Sarlo in the themes, conflicts and scenarios chosen by contemporary Argentine narrative. The analysis highlights the different types of functions of the ethnographic in the register of contemporary narratives, while at the same time it makes visible a certain model or matrix of critical (modernist) perception  in conflict with this formal emergence.
Keywords: Ethnofiction; Ethnography; Literature; Narrative; Culture